PENGGUNAAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN KEMANDIRIAN SISWA BELAJAR SENI BUDAYA - Yona Syaida Oktira; Ardipal Ardipal; Jagar Lumban Toruan (SENDRATASIK UNP, 2013)
Abstract The aim of this research was to describe the use of audio-visual media to improve the students’ independence in learning arts  and cultures subject. This was a qualitative research which used descriptive method. The sources of the data were the teacher and the students. The result of the research showed that the use of audio-visual media made learning process become more effective and made the students felt happy, be serious and focused on the material being explained. These had raised the students’ independence in learning so that they were willing to perform dancing, playing musical instruments and performing a drama in front of the class. Kata kunci:   Media, Audiovisual, Belajar, Seni Budaya.